Regulatory elements and transcriptional control of chicken vasa homologue (CVH) promoter in chicken primordial germ cells. Issue 1 (December 2017) - Jin, So; Lee, Bo; Hwang, Young; Lee, Hong; Rim, Jong; Han, Jae
Abstract Background Primordial germ cells (PGCs), the precursors of functional gametes, have distinct characteristics and exhibit several unique molecular mechanisms to maintain pluripotency and germness in comparison to somatic cells. They express germ cell-specific RNA binding proteins (RBPs) by modulating tissue-specificcis - andtrans -regulatory elements. Studies on gene structures of chickenvasa homologue (CVH ), a chicken RNA binding protein, involved in temporal and spatial regulation are thus important not only for understanding the molecular mechanisms that regulate germ cell fate, but also for practical applications of primordial germ cells. However, very limited studies are available on regulatory elements that control germ cell-specific expression in chicken. Therefore, we investigated the intricate regulatory mechanism(s) that governs transcriptional control ofCVH . Results We constructed green fluorescence protein (GFP) or luciferase reporter vectors containing the various 5′ flanking regions ofCVH gene. From the 5′ deletion and fragmented assays in chicken PGCs, we have identified aCVH promoter that locates at −316 to +275 base pair fragment with the highest luciferase activity. Additionally, we confirmed for the first time that the 5′ untranslated region (UTR) containing intron 1 is required for promoter activity of theCVH gene in chicken PGCs. Furthermore, using a transcription factor binding prediction, transcriptome analysis and siRNA-mediated knockdown, we have identified that a set of transcription factors play a role in the PGC-specificCVH gene expression. Conclusions These results demonstrate thatcis -elements and transcription factors localizing in the 5′ flanking region including the 5′ UTR and an intron are important for transcriptional regulation of theCVH gene in chicken PGCs. Finally, this information will contribute to research studies in areas of reproductive biology, constructing of germ cell-specific synthetic promoter for tracing primordial germ cells as well as understanding the transcriptional regulation for maintaining germness in PGCs.